2017
DOI: 10.1103/physrevd.96.052004
|View full text |Cite
|
Sign up to set email alerts
|

Search for new phenomena in dijet events using 37fb1 of pp collision data collected at

Abstract: Dijet events are studied in the proton-proton collision data set recorded at ffiffi ffi s p ¼ 13 TeV with the ATLAS detector at the Large Hadron Collider in 2015 and 2016, corresponding to integrated luminosities of 3.5 fb −1 and 33.5 fb −1 respectively. Invariant mass and angular distributions are compared to background predictions and no significant deviation is observed. For resonance searches, a new method for fitting the background component of the invariant mass distribution is employed. The data set is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
230
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(237 citation statements)
references
References 100 publications
6
230
1
Order By: Relevance
“…In summary, all of these results are in agreement with earlier differential cross-section measurements in the tt final states involving at least one lepton [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Those studies observed a "softer" p T spectrum for the top-quark final states, although the statistical and systematic FIG.…”
Section: Atlassupporting
confidence: 81%
See 1 more Smart Citation
“…In summary, all of these results are in agreement with earlier differential cross-section measurements in the tt final states involving at least one lepton [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Those studies observed a "softer" p T spectrum for the top-quark final states, although the statistical and systematic FIG.…”
Section: Atlassupporting
confidence: 81%
“…The signature of a tt final state is therefore determined by the W boson decay modes. The ATLAS [7][8][9][10][11][12][13][14] and CMS [15][16][17][18][19][20] [21]. The analysis presented here makes use of the allhadronic tt decay mode, where only top-quark candidates with high p T are selected.…”
Section: Introductionmentioning
confidence: 99%
“…We exclude events with a top in the final state (as in e.g. [84,91]), since top decays will generically not reconstruct into a single jet. We do include tops in the final state when calculating the Higgs widths and branching fractions.…”
Section: Total Width and Branching Ratiosmentioning
confidence: 99%
“…) M X to each flavor of quark-antiquark pair, but can also in principle have loop-induced decays to gluon pairs. In particular, they can be produced singly as dijet resonances via qq → X → qq, resulting in the most recent LHC bound of M X > 6.6 TeV assuming g A = g B [80][81][82][83][84][85]. However, in the context of the present paper the bounds will be somewhat weaker if g A < g B , as in the example model of the previous section.…”
Section: Comments On Collider Phenomenologymentioning
confidence: 84%